2020
DOI: 10.1002/bdr2.1860
|View full text |Cite
|
Sign up to set email alerts
|

Role of coxsackie‐adenovirus receptor in cardiac development and pathogenesis of congenital heart disease

Abstract: The coxsackie-adenovirus receptor (CAR) is a cell surface transmembrane protein originally recognized for its role as a binding site for coxsackie-and adeno-viruses. As such, it is believed to play an important role in pathogenesis of myocarditis. Other studies have suggested that CAR also plays an important role in embryonic development, which is not surprising given the strong expression of the receptor in heart, brain, liver, pancreas, kidney, small intestine, and various epithelia during development. A num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Epidemiologic studies done in the 1960s suggested an association between maternal enteroviral infection, particularly coxsackievirus B (CVB), and CHD [ 11 ]. Interestingly, the coxsackievirus and adenovirus receptor (CAR), through which CVB infects cardiomyocytes in myocarditis, is highly expressed in the developing heart and brain, playing a critical role in cardiac development during gestation [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies done in the 1960s suggested an association between maternal enteroviral infection, particularly coxsackievirus B (CVB), and CHD [ 11 ]. Interestingly, the coxsackievirus and adenovirus receptor (CAR), through which CVB infects cardiomyocytes in myocarditis, is highly expressed in the developing heart and brain, playing a critical role in cardiac development during gestation [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, although CAR is the main CVB receptor, different CVB serotypes rely on CAR to different extents. In general, CVB2, CVB4, and CVB6 use only CAR to mediate signal transduction; in contrast, CVB1, CVB3, and CVB5 bind to CAR and decay‐accelerating factor (DAF) (Hafenstein et al, 2007; Shafren et al, 1995; Sharma, Perry, & Eghtesady, 2021). Both CAR and DAF are known to be expressed in the heart suggesting different CVB serotypes can use different mechanisms to cause pathology (Lin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…All CVB subtypes appear to use the common Coxsackie and Adenovirus Receptor (CAR) for cell entry; there are subtle differences; however, in tropism of the viruses which have been attributed to use of possible alternate receptors such as decay‐accelerating factor (DAF) (Hafenstein et al, 2007; Shafren et al, 1995; Sharma, Perry, & Eghtesady, 2021). Given our observations following prenatal infection of mice with CVB3 and to confirm the preceding associations between CVB1 and CVB4 infection and developmental issues, we investigated phenotypic differences in mouse fetuses exposed to alternate subtypes of CVB focusing on CVB1, CVB3, and CVB4 only.…”
Section: Introductionmentioning
confidence: 99%
“…To perform in-depth studies of the role of CXADR in cardiac functions at different embryonic and adult stages, several conditional CXADR knockout mouse models have been generated ( Table 1 ). Research focusing on the role in cardiac development and pathogenesis using these conditional knockout models has been extensively reviewed [ 30 ], readers are encouraged to refer there.…”
Section: Cxadr Knockout and Overexpression Mouse Modelsmentioning
confidence: 99%